Improving the stability of peptidic radiotracers by the introduction of artificial scaffolds: which structure element is most useful?. (27th July 2015) - Bacher, Lisa; Fischer, Gabriel; Litau, Shanna; Schirrmacher, Ralf; Wängler, Björn; Baller, Marko; Wängler, Carmen
<x xml:space="preserve">Abstract</x> Peptidic radiotracers are highly potent substances for the specific in vivo imaging of various biological targets with Single Photon Emission Computed Tomography and Positron Emission Tomography. However, some radiolabeled peptides such as bombesin analogs were shown to exhibit only a limited stability, hampering a successful target visualization. One option to positively influence the stability of radiolabeled peptides is the introduction of certain artificial molecular scaffolds. In order to comparatively assess the influence of different structure elements on the stability of radiolabeled peptides and to identify those structure elements being most useful for peptide radiotracer stabilization, several monomeric and dimeric bombesin derivatives were synthesized, exhibiting differing molecular designs and the chelator NODAGA for 68Ga‐labeling. The radiolabeled peptides were evaluated regarding their in vitro stability in human serum to determine the influence of the introduced molecular scaffolds on the peptides' serum stabilities. The results of the evaluations showed that the introduction of scaffold structures and the overall molecular design have a substantial impact on the stabilities of the resulting peptidic radiotracers. But besides some general trends found using certain scaffold structures, the obtained results point to the necessity to empirically assess their influence on stability for each susceptible peptidic radiotracer individually.